Genetic and functional analyses of CTBP2 in anorexia nervosa and body weight regulation - Giuranna, Johanna; Zheng, Yiran; Brandt, Matthäus; Jall, Sigrid; Mukherjee, Amrita; Shankhwar, Soni; Renner, Simone; Kurapati, Nirup Kumar; May, Caroline; Peters, Triinu; Herpertz-Dahlmann, Beate; Seitz, Jochen; et al. (Molecular psychiatry, 2025)
The C-terminal binding protein 2 (CTBP2) gene (translational isoforms: CTBP2-L/S, RIBEYE) had been identified by a cross-trait analysis of genome-wide association studies for anorexia nervosa (AN) and body mass index (BMI). Here, we did a mutation analysis in CTBP2 by performing polymerase chain reactions with subsequent Sanger-sequencing to identify variants relevant for AN and body weight regulation and ensued functional studies. Analysis of the coding regions of CTBP2 in 462 female patients with AN (acute or recovered), 490 children and adolescents with severe obesity, 445 healthy-lean adult individuals and 168 healthy adult individuals with normal body weight detected 24 variants located in the specific exon of RIBEYE. In the initial analysis, three of these were rare non-synonymous variants (NSVs) detected heterozygously in patients with AN (p.Arg72Trp - rs146900874; p.Val289Met -rs375685611 and p.Gly362Arg - rs202010294). Four NSVs and one heterozygous frameshift variant were exclusively detected in children and adolescents with severe obesity (p.Pro53Ser - rs150867595; p.Gln175ArgfsTer45 - rs141864737; p.Leu310Val - rs769811964; p.Pro397Ala - rs76134089 and p.Pro402Ser - rs113477585). Ribeye mRNA was detected in mouse hypothalamus. No effect of fasting or overfeeding on murine hypothalamic Ribeye expression was determined. Yet, increased Ribeye expression was detected in hypothalami of leptin-treated Lepob/ob mice. This increase was not related to reduced food intake and leptin-induced weight loss. We detected rare and frequent variants in the RIBEYE specific exon in both patients with AN and in children and adolescents with severe obesity. Our data suggest RIBEYE as a relevant gene for weight regulation.
Online verfügbar: 07. November 2024
Gesehen am 03.06.2025